Chemistry and Biology of Indoles and Indazoles: A Mini-Review - Shafakat Ali, Nasir Ali; Ahmad Dar, Bashir; Pradhan, Vidya; Farooqui, Mazahar (Mini Reviews in Medicinal Chemistry, 2013)
The present review article is related with the method of preparation, importance and medicinal application of indole and indazoles. The studies of heterocycles is an evergreen field in the branch of organic chemistry and always attract the attention of chemists working not only in the area of natural products but also in the synthetic chemistry. Moreover many useful drugs have emerged from the successful investigation carried out in this branch. The derivatives of indoles and indazoles exhibits antibacterial, anticancer, antionidants, anti-inflammatory, antidiabetic, antiviral, atniproliferative, antituberculosis, antispermetogenic activity, antipsychotic drugs etc.
Keywords: Indoles